2013
DOI: 10.13172/2052-9651-1-2-1122
|View full text |Cite
|
Sign up to set email alerts
|

New insights into growth hormone�s actions on the macrophage: Implications for non-growth related actions of growth hormone

Abstract: hormonal and metabolic factors, including blood glucose levels, exercise, sex hormones, glucocorticoids and thyroid hormone. At the cellular level, the pleiotropic action of GH is elicited by its interaction with the GH receptor (GHR). GHR belongs to class I cytokine receptor superfamily that includes receptors for PRL, leptin and interleukins. The predicted molecular mass of GHR is ~70 kDa. An initiating event in this interaction is the activation of janus kinase 2 (JAK2), a GHR-associated tyrosine kinase. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
(45 reference statements)
0
2
0
5
Order By: Relevance
“…Interestingly, removal of the pituitary gland and thyroid/parathyroid glands from rats before infection with S. mansoni resulted in increasing worm burdens, worm development, oviposition, and miracidial development (15). Indeed, growth hormone and thyroid hormones have been demonstrated to directly induce iNOS expression and increase iNOS activity by influencing the maturation and function of immune cells, such as macrophages (29)(30)(31)(32)(33). These results strongly support the important role of NO in the development of Schistosoma.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, removal of the pituitary gland and thyroid/parathyroid glands from rats before infection with S. mansoni resulted in increasing worm burdens, worm development, oviposition, and miracidial development (15). Indeed, growth hormone and thyroid hormones have been demonstrated to directly induce iNOS expression and increase iNOS activity by influencing the maturation and function of immune cells, such as macrophages (29)(30)(31)(32)(33). These results strongly support the important role of NO in the development of Schistosoma.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, a defective expression of genes in the myeloid cell differentiation pathway was demonstrated in peripheral leukocytes of df/df mice compared to N mice 33 , further suggesting this inability of monocytes to migrate to tissues in the absence of GH. Conversely, Kumar and Menon 34 reported that in vivo GH treatment also enhances monocyte migration to tissue, which can improve the ability to fight infection in local tissues. This evidence, combined with our current findings, indicated that GH may exert a significant impact on the maturation, activation, and functionality of effector macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…2 Problematika penggunaan GH pada non-GHD adalah kontroversi terkait dosis dan saat memulai pemberian, kemungkinan efek samping jangka panjang yang diperkirakan dapat menyebabkan keganasan. 3,4 Mekanisme Kerja GH Pada tingkat sel, mekanisme kerja GH tergantung pada interaksi dengan reseptor GH, diikuti dengan aktivasi janus kinase-2 transduser dan aktivasi kaskade transkripsi sinyal. Efek GH terjadi pada jaringan seperti hepar, tulang, otot, sel adiposit.…”
Section: Pendahuluanunclassified
“…Efek GH terjadi pada jaringan seperti hepar, tulang, otot, sel adiposit. 3 Ekstraksi substansi GH dari lobus anterior berhasil pada tahun 1921 dan aplikasinya pada manusia dimulai tahun 1958. Sebagai pusat regulator endokrin post natal, GH mengkode 217 asam amino yang akan menyebabkan terjadinya pembelahan proteolitik dari sinyal peptida, menghasilkan rantai tunggal polipetoda 191 asam amino dengan berat molekul 22 kDa.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation